2014
DOI: 10.1302/0301-620x.96b11.34888
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising soft-tissue infections of the upper limb

Abstract: Necrotising soft-tissue infections (NSTIs) of the upper limb are uncommon, but potentially life-threatening. We used a national database to investigate the risk factors for amputation of the limb and death. We extracted data from the Japanese Diagnosis Procedure Combination database on 116 patients (79 men and 37 women) who had a NSTI of the upper extremity between 2007 and 2010. The overall in-hospital mortality was 15.5%. Univariate analysis of in-hospital mortality showed that the significant variables were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
3
18
3
Order By: Relevance
“…The mortality rate probably decreased due to improvement in awareness and treatment, both in surgical care and in critical care support [9]. The cumulative mortality rate described for upper extremity NSTIs is 18.3% (90 patients died out of 493 included patients in 8 studies), with rates as low as 9% and as high as 36% [6,[18][19][20][21][22][23][24]. The low mortality rate in this study might be caused by the relatively large group of intravenous drug user and type II NSTIs.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate probably decreased due to improvement in awareness and treatment, both in surgical care and in critical care support [9]. The cumulative mortality rate described for upper extremity NSTIs is 18.3% (90 patients died out of 493 included patients in 8 studies), with rates as low as 9% and as high as 36% [6,[18][19][20][21][22][23][24]. The low mortality rate in this study might be caused by the relatively large group of intravenous drug user and type II NSTIs.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Infections are not only more common in people with diabetes but can also be more severe than in those without diabetes. For instance, observational studies have shown diabetes to be associated with both increased rate of hospital admission and increased time spent in hospital because of infections; increased rates of admission to intensive care units; increased mortality for pneumonia, bloodstream infections, and influenza; [13][14][15][16] increased rates of amputation and death for necrotising limb infections; 17 and greatly increased rates of endogenous endophthalmitis among patients with fungaemia or bacteraemia. 18 Diabetes might also affect antibiotic treatment; it has been associated with increased antimicrobial drug resistance-eg, among Enterobacteriaceae 19-21 -whereas impaired kidney function and liver steatosis associated with diabetes increase the risk of antimicrobial drug toxicity.…”
Section: Diabetes Mellitus and Infectious Diseasesmentioning
confidence: 99%
“…Necrotizing soft tissue infections (NSTIs) are uncommon, severe, and potentially lethal conditions. 1,2 Surviving often comes at the prize of life-lasting morbidity. 3 NSTI typically presents with pain, swelling, and skin discoloration 4 .…”
Section: Necrotizing Soft Tissue Infectionsmentioning
confidence: 99%